The Response of Photosynthetic Functions of F1 Cutting Seedlings From Physocarpus amurensis Maxim (♀) × Physocarpus opulifolius “Diabolo” (♂) and the Parental Seedlings to Salt Stress - Nan, Xu; Huihui, Zhang; Haixiu, Zhong; Yining, Wu; Jinbo, Li; Li, Xin; Zepeng, Yin; Wenxu, Zhu; Yi, Qu; Guangyu, Sun (Frontiers in Plant Science, 2018)
This paper selected clonal cutting seedlings from the F1 hybrid varieties of Physocarpus amurensis Maxim (♀) × P. opulifolius “Diabolo” (♂) as research material to study the response of the photosynthetic gas exchange parameters and chlorophyll fluorescence parameters of P. amurensis hybrids and their parental leaves to NaCl stress (with concentrations of 0, 50, 100, and 200 mmol⋅L-1). The results showed that under salt stress, the stomatal conductance (Gs), transpiration rate (Tr), and net photosynthetic rate (Pn) of the three kinds of P. amurensis all significantly decreased. When the NaCl concentration was below 100 mmol⋅L-1, the intercellular CO2 concentration (Ci) of leaves of the three samples declined with the increase of salt concentration; however, when the concentration increased to 200 mmol⋅L-1, Ci did not decrease significantly, especially when the Ci of P. opulifolius “Diabolo” presented a slight increase. This indicated that the decline of photosynthetic carbon assimilation capacity induced by salt stress was the consequence of interaction between stomatal factors and non-stomatal factors, and the stomatal factors played an important role when the salt concentration was below 200 mmol⋅L-1. Compared with P. amurensis, the photosynthetic gas exchange capability of P. opulifolius “Diabolo” leaves was more sensitive to salt stress, and the limitation of non-stomatal factors was relatively evident. However, the photosynthetic capacity of hybrid P. amurensis leaves with the desired purple color was improved compared with P. amurensis. Under salt stress, the PSII activity of the three kinds of P. amurensis leaves declined, the electron transfer was inhibited, and obvious signs of photoinhibition were present. The PSII activity of P. opulifolius “Diabolo” leaves was more sensitive to salt stress than that in P. amurensis. Under salt stress, the NPQ of P. opulifolius “Diabolo” leaves decreased greatly, while under high salt concentrations the degree of photoinhibition in P. amurensis and hybrid P. amurensis were reduced due to a relatively high NPQ. With the increase of salt concentration, the Vk of P. amurensis and hybrid P. amurensis leaves presented a decreasing trend. However, the Vk of P. opulifolius “Diabolo” leaves increased slightly. This suggested that the effects of salt stress on the oxygen-evolving complex (OEC) of the three P. amurensis sample types were relatively limited and only the OEC of P.s opulifolius “Diabolo” leaves were slightly sensitive to salt stress. The VJ of all leaves from the three P. amurensis types increased under salt stress, and the VJ increased significantly when the salt concentration increased to 200 mmol⋅L-1, indicating that salt stress obviously impeded the electron transfer chain from QA to QB on the PSII receptor side. Moreover, high salt concentrations caused thylakoid membrane dissociation. The electron transfer and degree of damage to the thylakoid membrane of P. opulifolius “Diabolo” leaves were obviously higher than that of P. amurensis. However, the electron transfer capacity on the PSII receptor side as well as the degree of damage of the thylakoid membrane of hybrid P. amurensis leaves was obviously lower than those of P. opulifolius “Diabolo.” The salt tolerance of photosynthetic functions of hybrid P. amurensis (♀) × P. opulifolius “Diabolo” (♂) leaves was improved compared with that of parental P. opulifolius “Diabolo,” and the hybrid shows obvious hybrid vigor for photosynthesis.